Indo-US FTA: Prospects for the Telecommunication Sector - Arpita Mukherjee; Prerna Ahuja (Indian Council for Research on International Economic Relations (ICRIER), 2006)
Since telecommunication is one of the main drivers of economic growth and globalization, WTO (World Trade Organization) negotiations and New Age FTAs (Free Trade Agreements) have focused on liberalizing trade in this sector. The present paper analyses the possibilities of liberalizing trade in telecommunication services if India and its largest trading partner-the US-enter into a bilateral agreement. The study found that India and the US have trade complementarities in telecommunication services and that it should be a priority sector in the FTA negotiations. The study identified certain areas such as R&D related to telecommunication and broadband infrastructure where collaboration between companies of both countries would be mutually beneficial. The study found that telecommunication services have been significantly liberalized in the US FTAs-much beyond the scope of the GATS and the Reference Paper on Basic Telecommunications. While the current policy regime in India is consistent with some of the requests made by the US in its bilateral negotiations, for meeting others, the policy regime needs to be examined and, if required, reformed. The present paper suggests certain reforms which would enhance the productivity, efficiency and global competitiveness of the sector and enable the country to benefit from the bilateral liberalization.
Keywords: F13; F14; L96; 330; Indo-US FTA; GATS; bilateral agreements; telecommunication; services